Retrieval of Atmospheric CO2 and CH4 Variations Using Ground-Based High Resolution Fourier Transform Infrared Spectra - Tian Yuan; Liu Cheng; Sun You Wen; Xie Pin Hua; Wang Wei; Liu Wen Qing; Liu Jian Guo; Li Ang; Hu Ren Zhi; Zeng Yi (Journal of Spectroscopy)
High resolution Fourier transform near IR solar spectra are used to estimate the column-averaged dry-air mole fraction (DMF) of CO2 and CH4 variations in the atmosphere. The preliminary retrieval results for CO2 and CH4 variations in the area of Hefei, China, are presented, and the underlying error sources are also analyzed. Both a forward analysis and an inversion algorithm are included in the retrieval. The forward analysis uses the modeled atmospheric transmittance to line-by-line (LBL) convolute the instrument line shape function. The influences of the temperature, pressure, humidity, and a priori gases are considered in the atmospheric transmittance model. The inversion algorithm is based on the nonlinear iterative and nonlinear least squares spectral fitting, which is used to obtain VCDCO2 and VCDCH4 (which represent vertical column density of CO2 and CH4, resp.). Furthermore, the VCDO2 is also retrieved for converting the VCDs into DMFs. DMFs are final products of data analysis. The inversion results can clearly resolve the tiny variations of CO2 and CH4 under strong atmospheric background. Spectral fitting residuals for both VCDCO2 and VCDCH4 are less than 0.5%. Finally, CO2 and CH4 diurnal variations are investigated based on a typical observation. About 2 ppm amplitude for DMFCO2 diurnal variations and less than 15 ppb amplitude for DMFCH4 are observed.